Keggin Structure, Quō Vādis? - Kondinski, Aleksandar; Parac-Vogt, Tatjana N. (Frontiers in Chemistry, 2018)
Working under the supervisor of William Lawrence Bragg at the University of Manchester and being under the direct personal and scientific influence by Linus Pauling, Dr. James Fargher Keggin some ü years ago published a highly unique discovery – the structure of phosphotungstic acid (Nature 1933, 131, 908–909). This structure sparked the reports of other related polyanions from Keggin’s contemporaries, marking the true beginnings of structural polyoxometalate chemistry. In this perspective article, we unveil some aspects and applications of Keggin’s structure and discuss how it has shaped the course of our understanding of polyoxometalate chemistry and nanomolecular metal oxides/hydroxides in general.